2007
DOI: 10.1111/j.1460-9568.2007.05603.x
|View full text |Cite|
|
Sign up to set email alerts
|

Homeostatic plasticity in human motor cortex demonstrated by two consecutive sessions of paired associative stimulation

Abstract: Long-term potentiation (LTP) and long-term depression (LTD) underlie most models of learning and memory, but neural activity would grow or shrink in an uncontrolled manner, if not guarded by stabilizing mechanisms. The Bienenstock-Cooper-Munro (BCM) rule proposes a sliding threshold for LTP/LTD induction: LTP induction becomes more difficult if neural activity was high previously. Here we tested if this form of homeostatic plasticity applies to the human motor cortex (M1) in vivo by examining the interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
136
4
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 164 publications
(170 citation statements)
references
References 41 publications
24
136
4
1
Order By: Relevance
“…The current study demonstrated that plastic changes in the corticospinal system largely follow the rule of homeostatic metaplasticity by showing greater corticospinal excitability increases in the C-A group compared to S-A group, which is in agreement with previous studies using tDCS (Christova et al 2015) and other forms of NIBS protocols in healthy young adults (Iyer et al 2003, Muller et al 2007, Murakami et al 2012, Siebner et al 2004). …”
Section: Neurophysiological Effects Of Tdcs With the Cathode Placed Osupporting
confidence: 92%
See 1 more Smart Citation
“…The current study demonstrated that plastic changes in the corticospinal system largely follow the rule of homeostatic metaplasticity by showing greater corticospinal excitability increases in the C-A group compared to S-A group, which is in agreement with previous studies using tDCS (Christova et al 2015) and other forms of NIBS protocols in healthy young adults (Iyer et al 2003, Muller et al 2007, Murakami et al 2012, Siebner et al 2004). …”
Section: Neurophysiological Effects Of Tdcs With the Cathode Placed Osupporting
confidence: 92%
“…It appears that the human motor system is regulated by homeostatic metaplasticity mechanisms (Muller et al 2007, Murakami et al 2012, Siebner et al 2004). According to the Bienenstock-Cooper-Munro (BCM) theory of homeostatic metaplasticity (Bienenstock et al 1982), plasticity at a synapse is bidirectional, resulting in either LTP or LTD.…”
Section: Introductionmentioning
confidence: 99%
“…The intensity of TMS was adjusted to SI 1mV in the resting APB when given without the preceding median nerve stimulus. To produce a long lasting LTP-like increase in MEP amplitude the interstimulus interval was equal to the individual N20-latency of the median nerve somatosensory-evoked cortical potential plus 2 ms (N20 þ 2 ms) (Müller et al, 2007). The mean ( ± SD) interstimulus interval was 21.9 ± 0.6 ms.…”
Section: Paired Associative Stimulation (Pas Ltp )mentioning
confidence: 99%
“…PAS LTP was performed according to a protocol originally described by (Stefan et al, (2000)) and later on slightly modified by our group (Müller et al, 2007;Müller-Dahlhaus et al, 2008). It consisted of 225 pairs of electrical stimulation of the right median nerve at the wrist followed by TMS delivered at a rate of 0.25 Hz (duration: 15 min).…”
Section: Paired Associative Stimulation (Pas Ltp )mentioning
confidence: 99%
“…Bipolar electrical stimulation of the right median nerve at the wrist (cathode proximal, constant-current square pulses of 1 ms duration, intensity of three times the perceptual sensory threshold) preceded TMS of the hand area of the left M1 by the individually determined latency of the median nerve somatosensory evoked early cortical potential (N20) plus 2 ms. This interstimulus interval resulted in previous studies in consistent and reproducible LTP-like plasticity, that is, a long-lasting (430 min) on average 1.5-fold increase in MEP amplitude (Müller et al, 2007;Jung and Ziemann, 2009;Heidegger et al, 2010). The TMS intensity was adjusted to elicit on average peak-to-peak MEP amplitudes of 1 mV (MEP 1 mV ) when TMS was given alone.…”
Section: Induction Of Ltp-like Plasticity By Pasmentioning
confidence: 99%